Macro-Structural Obstacles to Firm Performance : Evidence from 2,640 Firms in Nigeria - Hosny, Amr (IMF Working Papers; Working Paper ;, 2020)
A recent World Bank enterprise survey identified access to finance as the top constraint to Doing Business in Nigeria. In this context, the objective of this paper is two-fold: (i) study firm characteristics associated with more access to finance and export diversification; and (ii) quantify the impact of these structural obstacles on firm performance. Results suggest that (i) larger and export-oriented firms are about 40 percentage points less likely to report access to finance as a business obstacle, while firms perceiving access to finance as a constraint are, on average, about 10-40 percentage points less likely to be export-oriented diversified firms; and (ii) better access to finance and export diversification can help firm employment -as much as 80 percent higher- and capacity utilization. Results are largely robust to different specifications and estimation methods.